Impact of Age and Sex on Bystander Cardiopulmonary Resuscitation Knowledge - Olutoyin Onyeaso, Adedamola; Oluferanmi Onyeaso, Onyeadikachi (International Journal of Scientific Research and Management (IJSRM), 2017)
AbstractObjective: To assess the impact of age and sex on the bystander CPR Knowledge in a group of Nigerian student teachers.Materials and Methods: A quasi-experimental study design was used with the cohort made up of forty one (41) male and forty one (41) female undergraduate students of Physical and Health Education with 40 participants in the 17-20 years age group and 42 participants belonging to the 21-28 years of age bracket were randomly selected from the larger main cohort for analysis of possible impact of age and sex on their pre-training and post-training cardiopulmonary resuscitation knowledge. In addition to the descriptive statistics, one-way analysis of variance (ANOVA) was used to test the null hypotheses generated with significance level set at P < 0.05.Results: No significant age impact was found on the pre-training and post-training CPR knowledge of the student teachers (P > 0.05). However, there was a positive impact of male gender on post-training CPR knowledge of the participants (P